Butterflies (Lepidoptera) of Guyana: A compilation of records - Sambhu, Hemchandranauth; Nankishore, Alliea (Zootaxa, 2018)
An examination of the available literature shows that a total of 1,205 butterfly species from 457 genera, 22 subfamilies and six families have been recorded in Guyana. Specimens that are unidentified above genus level and those that require further verification are excluded from this checklist. Although investigations have been conducted in all of the natural regions and administrative regions of Guyana, additional research is required on a number of aspects including species biology and behavioral ecology. It is hoped that this list will facilitate research on such data gaps.